Ultrathin structure of oxygen doped carbon nitride for efficient CO2 photocatalytic reduction. (23rd December 2021) - Zhong, Kang; Zhu, Xingwang; Yang, Jinman; Mo, Zhao; Qian, Junchao; He, Minqiang; Song, Yanhua; Liu, Jinyuan; Chen, Hanxiang; Li, Huaming; Xu, Hui
Abstract: Photocatalytic conversion of carbon dioxide into fuels and valuable chemicals is a promising method for carbon neutralization and solving environmental problems. Through a simple thermal-oxidative exfoliation method, the O element was doped while exfoliated bulk g-C3 N4 into ultrathin structure g-C3 N4 . Benefitting from the ultrathin structure of g-C3 N4, the larger surface area and shorter electrons migration distance effectively improve the CO2 reduction efficiency. In addition, density functional thory computation proves that O element doping introduces new impurity energy levels, which making electrons easier to be excited. The prepared photocatalyst reduction of CO2 to CO (116 μ mol g −1 h −1 ) and CH4 (47 μ mol g −1 h −1 ).